Sikap Konsumen Muslim terhadap Produk Ramah Lingkungan dalam Perspektif Maqashid Syariah - Fitriana, Dina; Kamarullah, Hasbi (Institute Agama Islam Tafaqquh Fiddin Dumai, 2025)
This study analyzed Muslim consumer attitudes towards environmentally friendly products from a Maqashid Syariah perspective in Balangan Regency. The problem addressed was the lack of in-depth understanding of how Islamic values influence sustainable consumption behavior. A quantitative approach using a survey method was employed, involving 150 Muslim respondents. Data were collected through structured questionnaires and analyzed using descriptive statistics. The findings indicated that Muslim consumers in Balangan Regency demonstrated a moderate understanding of Maqashid Syariah, high environmental awareness, high perception of the value of environmentally friendly products, and a high intention to purchase environmentally friendly products. These results suggest that Maqashid Syariah serves as a strong ethical foundation in shaping positive awareness and intentions among Muslim consumers towards sustainable products. The study concludes that the internalization of religious values, particularly Maqashid Syariah, plays a significant role in driving ecologically responsible consumption behavior.